USE AS AN ANTENNA cans amplifier BASED IN COMPUTER NETWORK ACCESS POINT - Nenny Anggraini Anggraini (JAKSTIK Journal, 2004)
Writing is about the use of tin as the antenna amplifier in a network without cables based onthe access point. Limited funds to implement a network, either wired or wireless antennasusing a major factor in the use of tin as a wireless antenna that can strengthen the wave fromthe receiving antenna (receiver) to the access point.Counting cans that will become an antenna to it that can not be ignored in order to obtain agood signal amplification.